2022
DOI: 10.3390/plants11030249
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and Morphological Responses of Sacha Inchi (Plukenetia volubilis L.) to Waterlogging Stress

Abstract: Sacha inchi (Plukenetia volubilis L.) is an important oilseed crop that is rich in fatty acids and protein. Climate-change-related stresses, such as chilling, high temperature, and waterlogging can cause severe production loss in this crop. In this study, we investigated the photosynthetic responses of sacha inchi seedlings to short-term waterlogging and their morphological changes after long-term waterlogging stress. Sacha inchi CO2 uptake, stomatal conductance, and transpiration rate are affected by temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Moisture in food is related to mineral ions, organic monomers, and polymers linked through hydrogen bonds. The quality of photosynthesis in the sacha inchi plant is also affected by waterlogging [ 1 ]. In addition, the role of moisture also involves the food fermentation process [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moisture in food is related to mineral ions, organic monomers, and polymers linked through hydrogen bonds. The quality of photosynthesis in the sacha inchi plant is also affected by waterlogging [ 1 ]. In addition, the role of moisture also involves the food fermentation process [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The distillate was collected in an Erlenmeyer flask containing 25 mL of 0.05 N H 2 SO 4 and 2 drops of indicators and then titrated with 0.05 N NaOH. The total protein content was calculated using Equation (1). Protein content analysis was performed for each sample with 18 repetitions.…”
Section: Ash Content Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The yield depends on the accumulation and distribution of photosynthetic substances, with temperature exerting a significant effect on the photosynthetic capacity of rice [ 7 , 8 ]. Studies have shown that a high temperature can reduce the leaf area index (LAI), chlorophyll content, and net photosynthetic rate (Pn), resulting in a decrease in dry matter accumulation (DMA) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Crops which are ideal for land particularly susceptible to recurrent extreme events should have sufficient photosynthetic flexibility to secure food despite such events. This problem is investigated by Chen et al, who exposed the tropical rainforest crop Plukentia volubilis to waterlogging stress and explored the possibility of selecting more tolerant lines based on their photosynthetic traits [ 15 ].…”
mentioning
confidence: 99%